Perbandingan Efek Asap Rokok Konvensional Dan Rokok Herbal Terhadap Motilitas Spermatozoa Mencit (Mus Musculus) - Negoro, Radityo Adi, dr. Retno Sintowati, M.Sc (2016)
The prevalence of smokers is increasing. Smokers in developing countries has increased, while in developed countries has decline in the number of smokers. More than 4700 of chemical compounds in cigarette smoke. The manufacturer of cigarette offers the herbal cigarettes include honey, siwak, betel leaf, green tea, srigunggu and there are also contain tobacco and cloves. Conventional cigarettes contain 2.4 of nicotine and 38mg of tar and Herbal cigarettes contain 0.3 mg of nicotine and 33.95 mg of tar. This study the researcher to determine the effect of exposure in conventional and herbal smoke of motility in mice (Mus musculus). In this study the researcher used the Post Test Only Control Group Design with the exposure period for 14 days to 30 mice were divided into 3 groups, in each group includes 10 animals. The groups are control group, conventional group and herbal group. While the parameters of observed is the motility in mice (Mus musculus) for all samples. The sampling technique used purposive sampling and the analyzed using Anova in SPSS 20 for windows. The results of analysis shows that the value of p = 0.000 (p <0.05), which means to have significant differences in each group. Both of group which exposure of conventional cigarette and group which exposure of herb cigarette has decline in motility. The effect caused of conventional cigarette in motility more bigger than effect herb cigarette.